From The Sea Wall to The Lover : Prostitution and Exotic Parody - Pascale Bécel (Studies in 20th & 21st Century Literature, 1997)
This analysis of the two novels highlights Marguerite Duras' equivocal stance with regard to colonial Indochina where she grew up at the beginning of the century. As The Lover rewrites The Sea Wall in the autobiographical mode, the emphasis shifts from an explicit denunciation of colonialism and an implicit subversion of the Lotilian novel, to a parody of exotic themes and narratives. However, by focusing on the two young protagonists' construction of themselves as femmes fatales and prostitutes, this discussion reveals that the politics of gender and race remain at odds in Duras' fictional autobiographies. The cultural other (qua a passive indigenous population in The Sea Wall, qua eroticized oriental[ized] bodies in The Lover) remains a measure of the protagonist's construction as a female subject; a measure, in Chandra Mohanty's words, of the "liberated" western woman's "discursive self-presentation."
Keywords: novel; Marguerite Duras; colonial Indochina; colony; colonization; The Lover; The Sea Wall; autobiographical mode; autobiographical; rewrite; colonialism; explicit; implicit; subversion; Lotilian novel; parody; parody of exotic themes and narratives; exotic themes; exotic narratives; young protagonist; construction of themselves; femmes fatales; prostitutes; politics of gender and race; gender; race; fictional autobiographies; passive indigenous population; indigenous; eroticized oriental[ized] bodies; other; oriental; female subject; Chandra Mohanty; liberated; discursive self-presentation; wester woman; feminism